Answer:
f(x) = x³ - x² - 4x + 4
Step-by-step explanation:
Given the zeros of a polynomial say x = a, x = b, x = c then
(x - a), (x - b), (x - c) are the factors of the polynomial and
f(x) is the product of the factors
here x = 1, x = - 2, x = 2, hence
(x - 1),(x + 2), (x - 2) are the factors and
f(x) = a(x - 1)(x + 2)(x - 2) ← a is a multiplier
let a = 1 and expand the factors
f(x) = (x - 1)(x² - 4)
= x³ - 4x - x² + 4
= x³ - x² - 4x + 4 ← in standard form
Answer:
$76.33
Step-by-step explanation
1 divided by 4/6 = 3/2 =1.5
50.89 x 1.5 =$76.33
Answer:
Step-by-step explanation:
4^2+x^2 = 15^2
x^2 = 15^2 - 4^2 = 225-16 = 209
x=sqrt(209)
x = 14.46
Plug in the coordinates (-2,-13) into the point slope formula with the slope remaining as 5x